A Telerobotic System for Transnasal Surgery of the Larynx and Upper Airways. (23rd August 2013) - Dharamsi, Latif M.; Bajo, Andrea; Netterville, James L.; Garrett, C. Gaelyn; Simaan, Nabil
Abstract : Objectives: The trend toward minimally invasive surgery has been an historic force driving the development of new surgical technique, specifically endoscopy. Transnasal endoscopic approaches to the larynx have been used but are limited by the precision and accuracy afforded to the surgeon. The objective of this study is to analyze and describe the feasibility, accuracy, and precision of a rapidly deployable telerobotic system for enabling transnasal microsurgery of the larynx and upper airways, specifically injection laryngoplasty. Methods: A feasibility study was conducted in which a tele‐operated system composed of a 5 degree of freedom continuum manipulator, 2 instrumentation ports, and a 1.2mm fiberoptic endoscope, to list a few key components, was deployed in both a human intubation trainer mannequin and cadaver using a nasopharyngeal airway as the conduit. Novel control algorithms assist the insertion by autonomously conforming the shape of the robot to the unknown curvature of the anatomy. A flexible needle was passed through the endoscope and used to target specific areas of the vocal folds to simulate injection laryngoplasty in our experimental models. Experiments were recorded with both still and video photography. Our outcome measure was the feasibility of this surgical approach. Results: This transnasal telerobotic system is well suited for surgery of the larynx and upper airways. Conclusions: Based on our preliminary results, our telerobotic system is suitable for accurate and precise injection laryngoplasty. We propose that such a system has widespread utility for additional surgical procedures of the larynx and upper airway.